Allergen-specific immunotherapy in the treatment of bronchial asthma in children - L.V. Besh; Z.L. Slyuzar (Zaslavsky O.Yu., 2019)
The article presents a review of the literature that analyses the current possibilities and benefits of allergen-specific immunotherapy in children with bronchial asthma. Bronchial asthma has a leading place in the structure of allergic pathology. According to the latest World Health Organization data, annually about 235-300 million people are diagnosed with it. It also belongs to those diseases that significantly reduce the quality of life of patients. Among children this pathology remains one of the most common diseases of the respiratory system, which is associated with the risk of disability and high mortality. Today, it has been proven that asthma pharmacotherapy can effectively control its symptoms, but it cannot affect the specific immune response and, if medication is discontinued, the symptoms of the disease may return. The only treatment that changes the natural course of allergy is allergen-specific immunotherapy, which reduces the sensitivity of the child's body to the "guilty" allergen and reduces the activity of chronic inflammation. Allergen-specific immunotherapy is carried out with the use of purified water-salt extracts of allergens or allergenic components distracted from them. This method of treatment usually involves the hypodermic or sublingual administration of gradually increasing amounts of "guilty" allergens to a dose that is effective in inducing immunological allergen tolerance. The evidence base for the effectiveness of allergen-specific immunotherapy in the treatment of bronchial asthma has expanded significantly in recent years. Obtained data today proved that such treatment allows changing the composition of cytokine markers, reducing the sensitivity of the respiratory canal to allergen exposure and preventing the expansion of the spectrum of causally significant allergens, slowing the progression of the allergic process, reducing the need for drugs. Moreover, today it can be argued that after successful courses of allergen-specific immunotherapy, long-term remission of bronchial asthma persists. The unique therapeutic effect of allergen-specific immunotherapy dictates the need for its widespread use in the treatment of bronchial asthma in children. For literature review, the following databases were studied: Medline, Web of Science, the Cochrane Library, Scopus.